PEMBELAJARAN TEKS PUISI KELAS X SMK KOPERASI PONTIANAK MENGGUNAKAN MODEL BLENDED LEARNING PADA MASA PANDEMI COVID-19 - Meri Mai Sari; Djon Lasmono; Martono Martono (Universitas Tanjungpura, 2022)
Mai Sari, Meri. 2022. “Learning Poetry Text for Class X SMK Koperasi Pontianak Using the Blended Learning Model During the COVID-19 Pandemic”. Thesis of the Department of Language and Arts Education. Faculty of Teacher Training and Education, Tanjungpura University. The first advisor Prof. Dr. H. Martono, M.Pd. and the second advisor Drs. Djon Lasmono, M.Pd.This research is a study on learning using the Blended Learning model. Blended Learning is a combination of face-to-face learning and online learning. The learning process during the COVID-19 pandemic underwent many changes, especially in the allocation of learning time. The problem raised in this research is the Indonesian language learning process which includes planning, implementation and assessment. This study used descriptive qualitative method. The data in this study were sourced from the Indonesian class X teacher. Based on the analysis of the planning, implementation and assessment of learning, it can be seen that the lesson plan (RPP) made by the teacher has been completely structured so that it reflects the essence of the learning process. Furthermore, in the process of implementing poetry text learning the first and third meetings were conducted offline while the second and fourth meetings were conducted online. Teachers and students experience difficulties, namely limited social interaction and limited learning time. Finally, the learning assessment carried out by the teacher is an assessment of knowledge and assessment of skills. Knowledge assessment is carried out during offline learning and is assessed based on student worksheets that have been done while skills assessment is carried out during online learning in the form of student work practices with the average result of students getting scores above the Minimum Completeness Criteria.